Production Management from Intelligent Models-Driven for Industry 4.0: Challenges and Opportunities - Ruiz-de la Peña, Jenny (2022)
In the past decade, the term Industry 4.0 has received increasing attention in both industry and academia. The manufacturing industry has evolved thanks to the digital revolution with the use of smart devices for intelligent manufacturing information systems. Working with intelligent production systems in this Industry 4.0 is a complex task that requires innovative ways of developing systems. One way to manage complexity is the use of intelligent model-driven engineering techniques. Although model-based approaches have several advantages and can be used to reduce complexity, studies to support Industry 4.0 are still limited. This article uses the bibliometric method to analyze the scientific performance of articles, countries, authors and journals based on the number of citations and cooperation networks. Most of the articles were published in conferences. The keywords industry 4.0 and model-driven engineering and embedded systems were the most used and represent the main areas of research. Most of the research related to the field was carried out in Austria and Germany. This study presents the evolution of the scientific literature on Industry 4.0 and intelligent model-based approaches and identifies areas of current research interest.